2019
DOI: 10.3390/ijms20071579
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Iberian Ribbed Newt Complement Component C3 by Stressors Similar to those Encountered during a Stay Onboard the International Space Station

Abstract: The complement system plays an important role in inflammation, innate and acquired immunity, as well as homeostasis. Despite these functions, the effects of spaceflight conditions on the complement system have not yet been intensively studied. Consequently, we investigated the effects of five types of chronic stressors, similar to those encountered during a stay onboard the International Space Station, on C3 expression in larvae of the urodele amphibian Pleurodeles waltl. We focused on C3 because it is a criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Thus, the modulation of inflammation, which is the immune system’s response to harmful stimuli and is a vital defense mechanism, likely contributes to explaining why nearly half of astronauts spending 6 months onboard the ISS face immunological problems ( 13 ). This modulation of inflammation is multifactorial because both bed rest used to simulate microgravity and the model used to mimic socioenvironmental stresses encountered inflight affect basal levels of cytokines involved in this biological process and is also observed in lower vertebrates in response to stressors similar to those encountered during a stay on the ISS ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the modulation of inflammation, which is the immune system’s response to harmful stimuli and is a vital defense mechanism, likely contributes to explaining why nearly half of astronauts spending 6 months onboard the ISS face immunological problems ( 13 ). This modulation of inflammation is multifactorial because both bed rest used to simulate microgravity and the model used to mimic socioenvironmental stresses encountered inflight affect basal levels of cytokines involved in this biological process and is also observed in lower vertebrates in response to stressors similar to those encountered during a stay on the ISS ( 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Modifications noted in these two subjects persisted during the whole mission and up to 30 days after landing, correlated with changes of the V(D)J recombination machinery, coincided with a higher stress response, and likely affected the specificities of the IgM binding sites. These alterations of the antibody repertoire, combined with other immune alterations such as changes in cytokine production, inflammation, and immune cell population distributions and function, 6,8,16,57‐59 could increase the clinical impact on the immune system. Challenge‐type experiments will need to be done to shed light on the consequences of these modifications of the antibody repertoire on immunocompetence and to estimate the effectiveness of inflight vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The development of P. waltl larvae under simulated microgravity or simulated microgravity and perturbed circadian rhythm also revealed modifications of the amounts of complement component 3 (C3) mRNAs and/or proteins, suggesting that complement expression can be modified under real spaceflight conditions, potentially increasing the risk of inflammation [ 62 ] and contributing to a better understanding of the inflammation observed during spaceflight [ 63 , 64 , 65 , 66 ]. More recently, Zhu and colleagues [ 67 ] showed that the retinoic acid-inducible gene (RIG)-I-like receptor (RLR) and Toll-like receptor (TLR) signaling pathways, essential for antiviral immunity, are significantly compromised in zebrafish embryos subjected to simulated microgravity.…”
Section: How Can Gepam Contribute To the Understanding Of Moleculamentioning
confidence: 99%